Ultimate CSI: Crime Scene Investigation - Marrinan, Corinne; Parker, Steve; Foreword by Bruckheimer, Jerry (London Dorling Kindersley Publishing, Inc., 2006)
This is a guide to all six series of this criminally good show. We've stalked, photographed, printed, tagged and bagged to bring you the inside story on the CSI Las Vegas graveyard shift. Get closer to the team you love, from Gil Grissom, Catherine Willows, Warrick Brown, Nick Stokes, Sara Sidle, Greg Sanders, to Dr Albert Robbins and Captain Jim Brass. Sneak a look at them working, with original close-ups straight from the show and learn what makes this extraordinary cast tick, their areas of expertise and the shocking cases that have got under their skin.
Include Illustrations, Glossary and Index.
Crime Scene Investigation.
Keywords: CSI, crime scene investigation (Television program) -- Forensic sciences